Efficient non-doped fluorescent OLEDs with nearly 6% external quantum efficiency and deep-blue emission approaching the blue standard enabled by quaterphenyl-based emitters. Issue 16 (11th April 2018) - Zeng, Weixuan; Zhao, Yongbiao; Ning, Weimin; Gong, Shaolong; Zhu, Zece; Zou, Yang; Lu, Zheng-Hong; Yang, Chuluo
Abstract : Two quaterphenyl derivatives are rationally designed and synthesized as deep-blue emitters to simultaneously afford outstanding device performance and excellent color purity approaching the NTSC blue standard. Abstract : Simultaneously achieving excellent color purity approaching or surpassing the blue standard and outstanding device performance remains a big challenge for blue fluorescent emitters. In this study, two quaterphenyl derivatives are rationally designed and synthesized as deep-blue emitters with high photoluminescence quantum yields of nearly 80%. These emitters are applied in non-doped OLEDs yielding a peak EQE of 5.94% and CIE coordinates of (0.152, 0.085), approaching the NTSC blue standard. When applied to doped OLEDs, these derivatives emit violet-blue light with a peak EQE of 6.55% and CIE coordinates of (0.156, 0.055).